The Environmental and Social Impacts of Urban Runoff on Eutrophic Lake Ecosystems - Roanhaus, Steven; Matthews, Samuel; Daniels, Gerald; Becker, Austin (My University, 2010)
Unraveling the issue of urban runoff is a daunting task to bring into focus because of difficulties identifying runoff sources and developing cost-effective solutions. The need to find solutions stems from issues of eutrophication that jeopardizes lake ecosystems and fish populations. The contributions come from sources ranging from residencies to businesses, and actors ranging from individuals to organizations. As the urban landscape expands, understanding surface and stormwater runoff is a necessity for responsible development and should take into account the resulting impacts on fish and the people who rely on them for sustenance.
Includes Bibliography, Maps, Figures, Graphs, Photographs.
Keywords: Eutrophic Lake; Ecosystems; Urban Runoff